COMPARATIVE ANALYSIS OF J. BYRON AND M. LERMONTOV’S POETRY - Ruzibayeva Aziza Kahramanovna (Western European Studies, 2024)
This article presents a comparative analysis of the poetry of two renowned poets, Lord Byron and Mikhail Lermontov. Through an examination of their themes, styles, and influences, this study seeks to illuminate the similarities and differences in their poetic works. By exploring how these two poets approach topics such as love, nature, and society, this analysis aims to offer insight into the unique contributions of Byron and Lermontov to the world of poetry.
Keywords: comparative analysis; Lord Byron; Mikhail Lermontov